Zeolite synthesis from industrial waste for bio-oil production / Maxmilan Bryan Daud and Dr Hamizura Hassan - Daud, Maxmilan Bryan; Hassan, Hamizura (2020)
In recent years, due to the escalation in global energy consumption, the impact of the conversion biomass-to-fuel processes have attracted the attention of scholars and policy makers. In this perspective, the production of bio-oil via pyrolysis process is an attractive method to achieve certain qualities of bio-oil. However, pyrolysis oil is less desirable due to high oxygen content, low calorific value and high water content, therefore, catalytic co-pyrolysis is introduced due to its numerous advantages. Although various catalytic systems have been evaluated for its production, the recent interest have indicate a shift towards industrial waste as another approach to improve the qualities of catalytic co-pyrolysis. The review therefore comprehensively explored the role of utilizing coal fly ash, woody biomass ash, palm oil mill fly ash, and sugarcane bagasse fly ash as heterogeneous catalyst for bio-oil production. In zeolite synthesis, concentration of alkaline source, temperature, reaction time, liquid/solid ratio and type of waste determine the structural properties, Si/Al ratio and its applications. The main characteristics and the applications of these synthesized waste zeolites are also reported. The paper further discussed the progress in terms of process mechanism and identification of active sites.